2016
DOI: 10.1021/jacs.6b00359
|View full text |Cite
|
Sign up to set email alerts
|

Activities and Stabilities of Au-Modified Stepped-Pt Single-Crystal Electrodes as Model Cathode Catalysts in Polymer Electrolyte Fuel Cells

Abstract: Details of experimental procedure Electrode preparationA Pt single crystal disk surfaced with a certain facet (hkl) (99.99%, 0.196 cm 2 , MaTecK) was annealed using electromagnetic inductive heating for 10 minutes at 1400 -1650 K in the flow of a mixture of H 2 and Ar (3 % H 2 , Taiyo Nippon Sanso, the purity of each gas: H 2 : 99.99999%, Ar: 99.999%). The annealed specimen was cooled slowly to room temperature in the flow of the same gas mixture and then, the (hkl) surface was covered with a droplet of ultrap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
48
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(50 citation statements)
references
References 77 publications
2
48
0
Order By: Relevance
“…In contrast, Au 0.6 /Pd 3 Fe(111) showed no observable potential shift after 500 ORR scans over the potential range of 50–1000 mV. The enhanced stability of the Au 0.6 /Pd 3 Fe(111) catalyst is consistent with the effect of Au on Pt catalysts previously reported ,. However, in these studies, the Au loading or coverage on Pt catalysts was kept very low to retain the activity of the catalyst.…”
Section: Figuresupporting
confidence: 87%
See 1 more Smart Citation
“…In contrast, Au 0.6 /Pd 3 Fe(111) showed no observable potential shift after 500 ORR scans over the potential range of 50–1000 mV. The enhanced stability of the Au 0.6 /Pd 3 Fe(111) catalyst is consistent with the effect of Au on Pt catalysts previously reported ,. However, in these studies, the Au loading or coverage on Pt catalysts was kept very low to retain the activity of the catalyst.…”
Section: Figuresupporting
confidence: 87%
“…A complication is that adsorbateinduced segregation of Pd from PdAu alloys has been well recognized. [26] Although Pd segregation cannot be excluded for these Au /Pd 3 Fe(111) surfaces, the poor ORR performance of both Pd-segregated PdAu alloy [27] and Pd-ML/Au(111) [28] electrocatalysts indicates that Pd segregation cannot explain the good ORR activity of the Au 0.6 /Pd 3 Fe(111) surface. Thus, we propose that the Au adatoms reconstruct from 2D islands into 3D nanoparticles during ORR.…”
mentioning
confidence: 99%
“…To this end, we are currently in the process of building an electrochemical cell which is directly attached to an UHV chamber. It would be of particular interest to probe whether the oxygen reduction activity might be related to defects such as surface steps [56][57][58] or surface cavities, [59] in addition to compressive strain.…”
Section: Discussionmentioning
confidence: 99%
“…24 Recently, Kodama and co-workers also demonstrated that Au as a vulnerable sites protector could improve the durability and activity of stepped Pt single-crystal. 26 Thus, these observations suggest a promising Au@Pt core-shell ORR catalyst with highly stable Au core and vulnerable sites protector which is generated by the spontaneously segregation of Au atoms onto the surface during electrochemical activation due to the lower surface energy of Au than Pt. 27 However, the lack of interest in the Au@Pt core-shell catalysts can be attributed to two impeding effects on ORR activity, that are, the strong bonding of OH and O to Pt due to the up-shifts of d-band center for Pt on Au core induced mainly by the strain effects, and the blocking of active sites of Pt due to too much Au segregation onto the Pt surface.…”
Section: Introductionmentioning
confidence: 90%